Chemical Characterization of Whiteboard Marker Inks Available in Nepal and Health Awareness among High School Teachers - Sharma, Surendra; Kharel, Madhav; Chalise, Baburam; Sharma, Khaga Raj; Gyawali, Deepak; Paudyal, Hari; Neupane, Bhanu Bhakta (Journal of Nepal Chemical Society, 2026)
Whiteboard markers are widely used in educational and professional environments due to their convenience and cleanliness compared with traditional chalk. This study evaluates the quality, compositional characteristics, and potential health risks associated with commercially available whiteboard marker inks from different brands. Elemental composition of the ink was determined using Energy-Dispersive X-ray Fluorescence (EDXRF), while Fourier Transform Infrared (FTIR) spectroscopy was employed to identify functional groups and solvent components. Gravimetric analysis was conducted to quantify solid and liquid components. In addition, a survey of 209 teachers was carried out to assess user awareness and reported health effects. The survey results revealed that a substantial proportion of teachers experienced health-related symptoms, including nasal irritation (34%) and eye irritation (18%), while 52.6% reported no prior awareness of the chemical constituents present in marker inks. Elemental analysis identified several metals, including copper (up to 3.8%), sulphur, silicon, and potassium, with certain brands also containing chromium or zinc, which may pose potential risks upon skin contact. FTIR analysis indicated that alcohol-based solvents, most consistent with ethyl and isopropyl alcohol. Gravimetric analysis further demonstrated notable variability in non-volatile material content across different brands. The combined analytical and survey findings highlight potential health concerns associated with exposure to volatile organic compounds and metal constituents in commonly used whiteboard marker inks. These results emphasize the need for safer ink formulations and increased awareness among users regarding potential chemical exposure.